THE PROSPECTS OF MICRO-INSURANCE IN THE RURAL AREAS OF NIGERIA - Aliero Haruna Mohammed; Shuaibu Mukhtar (European Scientific Journal, ESJ, 2012)
This study investigates the prospects of micro-insurance in the rural areas of Nigeria, while Kebbi State wasused as case study. The data used in this study is cross sectional and was collected from a sample of 190respondents, who were contacted through a structured questionnaire. The data collected was analyzed usinglogit regression model and the study revealed that income level, educational attainment and property ownershipas well as availability of infrastructural facilities in the rural areas, the prospects of Micro-Insurance in the ruralareas of Nigeria. The study recommended that income level of the rural dwellers should be taken intoconsideration while setting premium, efforts to provide, at least basic education in the areas, should beintensified it is also suggested that serious mobilization and sensitization should precede the introduction ofMicro-Insurance. Micro-insurance in rural areas should place more emphasis on farming, being the majoroccupation in the rural areas. As such we recommended for Agricultural Micro-insurance in rural Nigeria, atleast at start.